Photodynamic inactivation and mutagenesis by angelicin (isopsoralen) or thiopyronin (methylene red) in wild-type and repair-deficient strains of bacteriophage T4. - Drake, J W (1985)
Photodynamic inactivation of bacteriophage T4 particles, mediated by either angelicin or thiopyronin, is enhanced by defects in the T4 uvsW-uvsX-uvsY postreplication repair system but not by a defect in the denV pyrimidine-dimer-excision system. There was no evidence for functional interactions between the two repair systems. As observed previously with 8-methoxypsoralen, photodynamic mutagenesis with angelicin is abolished by defects in the uvsW-uvsX-uvsY system.